Effectiveness of Conflict Resolution Counseling for The Development of Peace Core Values on Vocational High School Students - Ilfiandra, Ilfiandra; Nadhirah, Nadia Aulia; Suryana, Dodi (Jurnal Bimbingan dan Konseling Terapan, 2023)
The research was motivated by the inability of students to resolve conflicts constructively, so many cases of conflict between students ended in violence. This study examines the effectiveness of conflict resolution counseling for developing core values of peace in adolescents. This research uses the positivism paradigm, quantitative approach, quasi-experimental method, and non-equivalent pre-test post-test control group design. The research participants were vocational high school students in the city of Bandung, totaling 63 people (32 people for the control and experimental groups), which were determined through a purposive technique. The data collection tool is a questionnaire on the core values of peace based on the U NESCO -APNIEVE Thurstone scale model with a reliability coefficient of 0.92. Data analysis to test the hypothesis using the One-Way ANOVA technique. The calculation results show that F hit = 3.401, at p = 0.070>0.05, dk = 1.58, which means that there was no significant difference in the core values of peace between the control group and the treatment group after conflict resolution counseling intervention. Partially, conflict resolution counseling effectively increases the three core values of peace: tolerance, recognition of other people's souls, and gratitude. The research recommendations are aimed at guidance and counseling teachers in vocational high schools.